IoT-Based Technology Solution for Monitoring Small Breed Cardiac Dogs with Heart Disease - Evangelista, Jeremias (2024)
Caring for geriatric small-breed dogs with heart disease from home is a challenge due to the lack of technological tools available in the market, specifically in South America. This lack limits the quality of life of these canine companions and hinders early detection of cardiac problems. Heart disease is common in geriatric dogs of small and medium breeds and the lack of accurate information about their health prevents proper care. In this study, a technological solution based on an IoT device is proposed for monitoring geriatric cardiac dogs in Peru. The device allows measuring temperature and heart rate and recording electrocardiograms in real time for early detection of cardiac problems in pets. For the development of the technological solution, a methodology based on four phases was applied: (1) Analysis of IoT devices, (2) Construction of IoT devices, (3) System construction and (4) System validation. Two experiments were conducted in a private veterinary medical center with two small-breed geriatric dogs with heart diseases, in which each dog had its Temperature (T) and Heart Rate (HR) measured in real-time. Comparing the results of both experiments, the temperature parameter had a better accuracy with an error rate (er) of less than 1%, compared to the average error rate of 7.95% for heart rate. In addition, a survey of veterinarians' experience with the resulting system showed high scores for usability and monitoring, confirming the potential of IoT systems for monitoring geriatric small breed dogs with cardiac problems with the novelty of being a low-cost, usable and reliable device.